Vocal Technique and Expressive Interpretation in the Performance of â€œGanjang Ma Umurmiâ€ by Osen Hutasoit - Andreas Simanjuntak; Hendrik L Simanjuntak; Happy Majesty Waruwu (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This study examines vocal technique and expressive interpretation in the performance of the Batak popular song â€œGanjang Ma Umurmiâ€ composed by Osen Hutasoit. While previous studies on vocal performance primarily emphasize technical mastery in classical or choral contexts, limited scholarly attention has been given to the integration of vocal technique and interpretative expression in contemporary Batak popular repertoire. This research aims to analyze how technical elementsâ€”posture, diaphragmatic breathing, articulation, intonation, resonance, and dynamicsâ€”function not only as mechanical vocal strategies but also as embodied expressive devices that shape musical meaning. Employing a qualitative descriptive approach, data were collected through performance observation, in-depth interviews, score analysis, and documentation of a recital performance at GBI Pelita IV. The data were analyzed using Miles and Hubermanâ€™s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the effective performance of this song requires a synergistic integration between technical control and emotional interpretation, particularly in handling modulation, sustained high-register passages, and dynamic contrast. Vocal technique operates as an expressive medium that constructs intimacy, sincerity, and emotional resonance within the performance. This study contributes to the discourse on vocal pedagogy and performance studies by highlighting the role of embodied technique in shaping interpretative meaning in regional popular music. The novelty of this research lies in its contextual focus on Batak popular repertoire and its analytical integration of technical and expressive dimensions in performance practice